TINJAUAN GENDER IDENTITY - RESPON DAN PERSEPSI TERHADAP IKLAN TELEVISI - Whidya Utami (EKUITAS (Jurnal Ekonomi dan Keuangan), 2004)
This paper seeks lo challenge the tendency lo represent gender as a unitary theoretical construct, and would argue for  a more  di.fjerentiated  view  of  how  the psychological aspect of gender influence the perception  of advertising This paper use a small-scale exploratory study  to examine  the potential  impact  o,f'gender  identity  within  consumer' self - schemas on their perception of advertising. Bern's ,)'ex Role Inventory (SRI) was administered to 20 young adults who then watched video  clips  of  television advertisements. The focus group discussions about  the  advertisements  were  analyzed within the context of the respondents ' gender schemas identified via the Bern SRI score: masculine. feminine, androgynous or und(tferentiated. The centrality of gender identity to self-schemas affected how consumers processed and interpreted the advertising. This provides support for a more differentiated approach to representing  men  and  women within gender research and advertising.